PELAKSANAAN SISTEM PENGURUSAN JAMINAN HALAL DI RUMAH-RUMAH SEMBELIHAN AYAM HALAL DAN ISU-ISU BERKAITAN: SATU SOROTAN LITERATUR: The Implementation of Halal Assurance Management System in Malaysia’s Certified Halal Slaughter Houses and Its Related Issues: A Literature Review - Razaly, Muhammad Mazuan; Zakaria, Zalina (Journal of Shariah Law Research, 2018)
A continuous halal control through the implementation of Halal Assurance Management System (HAS) needs to be properly executed to ensure that the process meets the halalan toyyiba aspects. The halal processing chain, especially at slaughtering premises, are very vulnerable to inaccuracy. The failure of the industry to meet the halalan toyyiba aspects can adversely affect the quality of the slaughtered products and even more serious, a non-halal slaughter. Hence, the study was conducted to examine the implementation of HAS by the industry and to address the issues related to its implementation. In order to ensure that the gathering of information process is working smoothly, this qualitative study uses three important instruments ie document analysis involving journals and scientific writing, interviews and followed by field observations. The outcome of this study is expected to be the basis for improving the quality of halal regulation management internally and also assisting in the enhancement of halal management at the Jabatan Kemajuan Islam Malaysia (JAKIM) level.